2002
DOI: 10.1093/emboj/cdf357
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 is activated transiently and targets Cdc25A for degradation at the Xenopus midblastula transition

Abstract: In Xenopus embryos, cell cycle elongation and degradation of Cdc25A (a Cdk2 Tyr15 phosphatase) occur naturally at the midblastula transition (MBT), at which time a physiological DNA replication checkpoint is thought to be activated by the exponentially increased nucleo‐cytoplasmic ratio. Here we show that the checkpoint kinase Chk1, but not Cds1 (Chk2), is activated transiently at the MBT in a maternal/zygotic gene product‐regulated manner and is essential for cell cycle elongation and Cdc25A degradation at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
187
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(200 citation statements)
references
References 48 publications
10
187
2
1
Order By: Relevance
“…Interestingly, Shimuta et al (2002) showed that Cdc25A in Xenopus is phosphorylated on Ser 73 (Ser 76 in human Cdc25A) by an unknown kinase. This phosphorylation is required for Chk1-induced degradation of Cdc25A and primes Cdc25A for degradation both in a normal cell cycle and in response to DNA damage.…”
Section: Cdc25a and Checkpointsmentioning
confidence: 99%
“…Interestingly, Shimuta et al (2002) showed that Cdc25A in Xenopus is phosphorylated on Ser 73 (Ser 76 in human Cdc25A) by an unknown kinase. This phosphorylation is required for Chk1-induced degradation of Cdc25A and primes Cdc25A for degradation both in a normal cell cycle and in response to DNA damage.…”
Section: Cdc25a and Checkpointsmentioning
confidence: 99%
“…Similar to the regulation of Twine, Cdc25A is abruptly degraded at the MBT in Xenopus, 26 although as with String, the degradation is regulated by Chk1, which is transiently activated coincident with the start of the MBT. 27 In Xenopus, Cdc25A degradation alone does not affect the MBT, since overexpression of a stabilized Cdc25A does not change the cell cycle length at the MBT. 27,28 However, phosphorylation of Cdc25A by Chk1 inactivates it, and this inactivation is essential for establishing the MBT.…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 98%
“…27 In Xenopus, Cdc25A degradation alone does not affect the MBT, since overexpression of a stabilized Cdc25A does not change the cell cycle length at the MBT. 27,28 However, phosphorylation of Cdc25A by Chk1 inactivates it, and this inactivation is essential for establishing the MBT. 28 Thus, both inactivation and degradation are likely to be involved in regulating Cdc25 in vertebrates (Fig.…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, activated Chk1 slows progression through S phase by blocking the firing of unfired origins of the replication (22)(23)(24)(25). In this checkpoint, Chk1 phosphorylates Cdc25A, leading to Cdc25A degradation (24,26,27). Because Cdc25A is required for activation of Cdk2 complexes, which then control the firing of origins of replication, activation of this pathway blocks S phase progression (28 -31).…”
mentioning
confidence: 99%